2004
DOI: 10.1021/jo049655z
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-Catalyzed Asymmetric Hydrogenation of Functionalized Olefins Using Monodentate Spiro Phosphoramidite Ligands

Abstract: Novel chiral monodentate phosphorus ligands, SIPHOS, were conveniently synthesized from 1,1'-spirobiindane-7,7'-diol. The Rh complexes of SIPHOS can catalyze the hydrogenation of alpha-dehydroamino esters in mild conditions, providing alpha-amino acid derivatives in up to 99% ee. Enamides and beta-dehydroamino esters can also be hydrogenated in good to excellent enantioselectivities (up to 99% and 94% ee, respectively). The SIPHOS ligand with smaller alkyl groups on the N-atom afforded higher enantioselectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
2
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 65 publications
1
36
2
4
Order By: Relevance
“…Zhou and co-workers [147] reported a highly enantioselective hydrogenation using Rh complexes of the siphos ligand (164) [Eq. (51); cod = cyclooctadiene].…”
Section: Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou and co-workers [147] reported a highly enantioselective hydrogenation using Rh complexes of the siphos ligand (164) [Eq. (51); cod = cyclooctadiene].…”
Section: Reviewsmentioning
confidence: 99%
“…[147] Only one ligand was suggested to be bonded to the rhodium center in the active catalyst (ML model). [147] However, this is unlikely in view of the mechanistic studies of Reetz, Blackmond, et al [145] A strong (+)-NLE was observed in the asymmetric hydrogenation of ethyl acetoacetate promoted by [(binap)-Ru(Br) 2 ] prepared in situ from scalemic (S)-binap [165; Eq. (52)].…”
Section: Reviewsmentioning
confidence: 99%
“…60 Some recently developed monodentate axial chiral P-ligands induced remarkably high enantioselectivities in the Rhcatalyzed enantioselective alkene hydrogenation, even comparable with those obtained using the best bidentate phosphines. 61 Monophosphines with axial chirality, e.g., MOP -(2 0 -methoxy-1,1 0 -binaphthyl-2-yl)diphenylphosphine family ligands, 62 and other monodentate binaphthyl-based ligands, as well as diaryl-63 and diheteroaryl-backbone ligands, or similar to them monodentate phosphorus ligands with a spiro scaffold [64][65][66] are widely used for transitionmetal-catalyzed asymmetric C À ÀC bond hydrogenation. [67][68][69] Selected examples of those types of ligands are shown in Figure 29.4.…”
Section: Diaryl-based Monodentate Ligands With Axialmentioning
confidence: 99%
“…The rhodium complex containing a SIPHOS ligand 1a is also an efficient catalyst for the asymmetric hydrogenation of cyclic enamides (Scheme 8.5). Under the conditions of 100 bar H 2 at 0 C in toluene, N-(1,2-dehydro-1-indanyl)acetamides 11a-11c were hydrogenated to the corresponding cyclic amines 12a-12c with 94, 88, and 95% ee, respectively [23].…”
Section: Asymmetric Hydrogenation Of Enamidesmentioning
confidence: 99%